PENERAPAN PROBLEM BASED LEARNING DALAM UPAYA MENINGKATKAN HASIL BELAJAR SISWA KELAS 1 SD DALAM PEMBELAJARAN PENDIDIKAN PANCASILA - Martanti, Windhi Tri; Wahdan Najib Habibiy; Esti Ambarwati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this research is to improve the learning outcomes of grade I elementary school students in the Pancasila education subject by using Problem Based Learning (PBL). The type of research used in this research is Classroom Action Research (PTK). The analysis technique in this research uses qualitative and quantitative analysis. The research subjects were 28 class I B students at SD Muhammadiyah PK Kottabarat. Based on the results of research and discussion, it shows that in the pre-cycle, student completeness was 17.86%, then in cycle I, student completeness was 53.47%, there was an increase of 35.61%, and in cycle II, student completeness was 100%. an increase of 46.53%. Thus, there is an increase in student learning outcomes in the Pancasila Education subject using the problem based learning (PBL) learning model.